2013
DOI: 10.1371/journal.pone.0083290
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Entner-Doudoroff Pathway with MEP Increases Isoprene Production in Engineered Escherichia coli

Abstract: Embden-Meyerhof pathway (EMP) in tandem with 2-C-methyl-D-erythritol 4-phosphate pathway (MEP) is commonly used for isoprenoid biosynthesis in E. coli. However, this combination has limitations as EMP generates an imbalanced distribution of pyruvate and glyceraldehyde-3-phosphate (G3P). Herein, four glycolytic pathways—EMP, Entner-Doudoroff Pathway (EDP), Pentose Phosphate Pathway (PPP) and Dahms pathway were tested as MEP feeding modules for isoprene production. Results revealed the highest isoprene productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 27 publications
0
59
0
Order By: Relevance
“…The low baseline carbon partition towards secondary metabolisms like terpene biosynthesis requires metabolic designs to efficiently channel photosynthates towards terpene biosynthesis precursors. In particular, the ratio of G3P and pyruvate was found to be essential for an increased terpene yield (Liu et al ., ). The redesign of photosynthesis pathways to generate an appropriately balanced G3P and pyruvate ratio thus may lead to more carbon partition into terpene biosynthesis.…”
Section: Key Technical Barriers and Improvement Strategies In Photosymentioning
confidence: 97%
“…The low baseline carbon partition towards secondary metabolisms like terpene biosynthesis requires metabolic designs to efficiently channel photosynthates towards terpene biosynthesis precursors. In particular, the ratio of G3P and pyruvate was found to be essential for an increased terpene yield (Liu et al ., ). The redesign of photosynthesis pathways to generate an appropriately balanced G3P and pyruvate ratio thus may lead to more carbon partition into terpene biosynthesis.…”
Section: Key Technical Barriers and Improvement Strategies In Photosymentioning
confidence: 97%
“…To increase the intracellular concentration of these two metabolites, we modulated central carbon metabolism by engineering the glucose transport system (De Anda et al, 2006), overexpressing tpiA (Choi et al, 2010), edd/eda (Liu et al, 2013), talA/tktB (Song et al, 2006), ppsA (Farmer and Liao, 2001), and pckA (Farmer and Liao, 2001), and knocking out gdhA (Alper et al, 2005) and pykF (Toya et al, 2010). Using galactose permease system to replace phosphoenolpyruvate:carbohydrate phosphotransferase system (PTS) to transport glucose has been reported to increase the concentration of phosphoenolpyruvate (PEP) and G3P (Escalante et al, 2010;Zhang et al, 2013)_ENREF_28.…”
Section: Modulating Central Metabolism For Improved β-Carotene Producmentioning
confidence: 99%
“…Among them, the modulation of glucose transport system , the overexpression of edd/eda operon (Liu et al, 2013) and tpiA gene (Choi et al, 2010), and the deletion of gdhA (Alper et al, 2005) were previously reported targets. On the other hand, the overexpression of talA/tktB operon and the deletion of pykF gene were novel targets in this study.…”
Section: Engineering Central Metabolic Pathways For β-Carotene Overprmentioning
confidence: 99%
“…Liu et al . () revealed that this problem could be resolved by enhancing the Entner–Doudoroff Pathway, which generates the same moles of pyruvate and G3P, the isoprene titre and yield were more than three and six times higher than those yielded with the EMP module respectively.…”
Section: Balancing Of the Precursors And Blocking Of The Competing Pamentioning
confidence: 99%
“…Introducing foreign genes associated with isoprenoid synthesis made it possible to generate desired products in bacteria. Many researchers explored synthetic biology methods of isoprenoid production by introducing heterologous isoprenoid synthase into bacteria (Zhao et al 2011;Yang et al 2012;Liu et al 2013;Bentley et al 2014). The isoprene synthase (ispS) gene catalyses the conversion of DMAPP to the isoprene (Silver and Fall 1991), so the ispS gene was introduced into Escherichia coli and a synthetic pathway of isoprene was constructed (Bentley et al 2014).…”
Section: Introductionmentioning
confidence: 99%